PENGARUH INDEPENDENSI, PENGALAMAN, DUE PROFESSIONAL CARE, DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT (Studi Kasus Kantor BPK Perwakilan Yogyakarta) - , Diah Ayu Susanti ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In accordance with the Regulation of the State Audit Board (BPK) of the Republic of Indonesia No.. 01, 2007 on State Auditing Standards, in article 1 explained that the management of state finances is the entire financial management activities of state officials in accordance with the position and authority include the planning, implementation, monitoring and accountability. This study is quantitative, because the study sought to reveal the facts in depth about the independence, experience, due professional care, accountability, quality audits. Data collection methods used were sent questionnaires directly to the auditor who worked on the BPK Representative Yogyakarta, that is to be able to explore the influence of anything that could affect the quality of audits produced by the auditor during the audit process. This study successfully demonstrated that the results of testing the independence and experience had no effect on audit quality, because that count less than 5% t table. While due professional care and accountability effect on audit quality because t count is greater than t table 5%